Correlation Between Physical Activity and Fitness Level Among Anesthesiology and Intensive Care Residents - Firdaus, Wildan; Fuadi, Iwan; Erlangga, M. Erias (Faculty of Medicine, Universitas Padjadjaran, 2023)
Anesthesiologists have a highly varied scope of work. Previous studies demonstrated that the physical activity of anesthesiologists and their residency program in the work environment does not meet the recommended standards. This study aimed to determine the relationship between physical activity and level of physical fitness among anesthesiology residents. This study was an analytical observational study with a cross-sectional design conducted on residents of Anesthesiology and Intensive Care, Faculty of Medicine, Universitas Padjadjaran, Indonesia, between January and April 2022. All anesthesiology residents were asked to fill out the International Physical Activity Questionnaire (IPAQ) and had their number of steps measured using a pedometer while the physical fitness level was assessed using the Harvard Step Test. Physical activity was assessed based on the IPAQ and pedometer. The results of IPAQ measurement showed that more subjects had low physical activity (n=44) compared to good physical activity (n=31). When measured using a pedometer, 38 subjects were classified as having low physical activity while 36 had good physical activity. Low fitness level (n=43) was associated with less physical activity on IPAQ (41 and 2)and pedometer (30 and 13). No residents had moderate or better fitness levels. Correlation analysis between physical activity and physical fitness showed a significantpositive correlation with a p-value <0.05 (Spearman Rho: 0.618). Thus,physical activity and fitness level are well-correlated among of Anesthesiology and Intensive Care residents.